2013
DOI: 10.1155/2013/214128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Epidemiology of Reduced Kidney Function among Elderly Male Fishing and Agricultural Population in Taipei, Taiwan

Abstract: Purpose. To quantify the prevalence of and associated factors for chronic kidney disease (CKD) among male elderly fishing and agricultural population in Taipei, Taiwan. Methods. Subjects (n = 2,766) aged 65 years and over voluntarily admitted to a teaching hospital for a physical checkup were collected in 2010. CKD was defined as an estimated glomerular filtration rate <60 mL/min/1.73 m2. Results. Among these subjects, the over prevalence of chronic kidney disease was 13.6% (95% CI: 12.3–14.9%). The age-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Renal functional decline is an important cause of hyperuricemia due to reduced uric acid clearance. 12 We found that the indicators of decreased renal function including eGFR, serum homocysteine, serum urea and Scr were significantly different between the hyperuricemia group and the normouricemia group. In addition, a low eGFR and a high serum urea level were independent risk factors for hyperuricemia.…”
Section: Discussionmentioning
confidence: 69%
“…Renal functional decline is an important cause of hyperuricemia due to reduced uric acid clearance. 12 We found that the indicators of decreased renal function including eGFR, serum homocysteine, serum urea and Scr were significantly different between the hyperuricemia group and the normouricemia group. In addition, a low eGFR and a high serum urea level were independent risk factors for hyperuricemia.…”
Section: Discussionmentioning
confidence: 69%
“…Prevalence of CKD also increases in age [28]. Hyperuricemia may be one of the strongest risk factors related to CKD in elderly population [29]. The elderly population has a higher level of SUA and a high risk of developing CKD [12].…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure was measured twice for each subject in the sitting position, with an interval of 15 minutes between measurements, using a standard sphygmomanometer of appropriate width after a rest period for 30 minutes. Those taking antihypertensive therapy were considered to have known hypertension 8. Fasting blood samples were drawn via venipuncture by clinical nurses.…”
Section: Methodsmentioning
confidence: 99%
“…Those taking antihypertensive therapy were considered to have known hypertension. 8 Fasting blood samples were drawn via venipuncture by clinical nurses. Overnight fasting serum and plasma samples (from whole blood preserved with ethylenediamine tetraacetic acid and sodium fluoride) were kept frozen at −20°C until ready for analysis.…”
Section: Methodsmentioning
confidence: 99%